2021
DOI: 10.21203/rs.3.rs-296518/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of CT-P59 plus standard of care: a phase 2/3 randomized, double-blind, placebo-controlled trial in outpatients with mild-to-moderate SARS-CoV-2 infection

Abstract: CT-P59, a monoclonal antibody with potent neutralizing activity against severe acute respiratory syndrome coronavirus 2, may ameliorate symptoms and prevent hospitalization in outpatients with mild-to-moderate disease. We report findings from part one of a two-part randomized, placebo-controlled, double-blind study (NCT04602000; EudraCT: 2020-003369-20). Outpatients with mild-to-moderate COVID-19 received a single dose of CT-P59 40 mg/kg (n=101), CT-P59 80 mg/kg (n=103), or placebo (n=103). Median (95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 13 publications
(15 reference statements)
0
34
0
2
Order By: Relevance
“…In a part 1 of a phase II/III trial (NCT04602000) (Sect. 2.3.2 ) in patients with mild-to-moderate SARS-CoV-2 infection, regdanvimab pharmacokinetics following a single 90-min IV infusion was characterized by a low clearance (0.227 mL/kg for 40 mg/kg), small volume of distribution (87.2 mL/kg for 40 mg/kg) and a terminal half-life of 12 days [ 1 , 17 ]. Regdanvimab is likely to be eliminated through normal immunoglobulin degradation pathways and the clearance is not expected to be affected by renal or hepatic impairment [ 1 ].…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In a part 1 of a phase II/III trial (NCT04602000) (Sect. 2.3.2 ) in patients with mild-to-moderate SARS-CoV-2 infection, regdanvimab pharmacokinetics following a single 90-min IV infusion was characterized by a low clearance (0.227 mL/kg for 40 mg/kg), small volume of distribution (87.2 mL/kg for 40 mg/kg) and a terminal half-life of 12 days [ 1 , 17 ]. Regdanvimab is likely to be eliminated through normal immunoglobulin degradation pathways and the clearance is not expected to be affected by renal or hepatic impairment [ 1 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…The efficacy of regdanvimab in the treatment of mild-to-moderate COVID-19 was evaluated in a randomized, double-blind, placebo-controlled, multinational phase II/III trial (NCT04602000), which was divided in two parts: part 1 (phase II) and part 2 (phase III). Currently, part 1 results are available and regdanvimab was effective in this part [ 17 ]. Eligibility criteria included: age ≥ 18 years; SARS-CoV-2 infection confirmed by quantitative reverse transcription polymerase chain reaction (RT-qPCR); > 94% oxygen saturation on room air and not requiring supplemental oxygen; and, onset of symptoms (feverishness, cough, shortness of breath, sore throat, body/muscle pain, nausea, fatigue, headache, chills, nasal congestion, loss of taste or smell, or diarrhoea) within 7 days prior to study drug administration.…”
Section: Scientific Summarymentioning
confidence: 99%
“…The supplementary data present the assessment of risk of bias of the included studies for each outcome. Twelve trials5054566065677286 proved at low risk of bias for all domains. All other studies proved at probably high or high risk of bias for at least one domain.…”
Section: Resultsmentioning
confidence: 96%
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation